Effectiveness of electrical stimulation therapy in improving arm function after stroke: a systematic review and a meta-analysis of randomised controlled trials. (August 2019) - Yang, Jheng-Dao; Liao, Chun-De; Huang, Shih-Wei; Tam, Ka-Wai; Liou, Tsan-Hon; Lee, Yu-Hao; Lin, Chia-Yun; Chen, Hung-Chou
Objective: The aim of this study is to investigate the effectiveness of electrical stimulation in arm function recovery after stroke. Methods: Data were obtained from the PubMed, Cochrane Library, Embase, and Scopus databases from their inception until 12 January 2019. Only randomized controlled trials (RCTs) reporting the effects of electrical stimulation on the recovery of arm function after stroke were selected. Results: Forty-eight RCTs with a total of 1712 patients were included in the analysis. The body function assessment, Upper-Extremity Fugl-Meyer Assessment, indicated more favorable outcomes in the electrical stimulation group than in the placebo group immediately after treatment (23 RCTs ( n  = 794): standard mean difference (SMD) = 0.67, 95% confidence interval (CI) = 0.51–0.84) and at follow-up (12 RCTs ( n  = 391): SMD = 0.66, 95% CI = 0.35–0.97). The activity assessment, Action Research Arm Test, revealed superior outcomes in the electrical stimulation group than those in the placebo group immediately after treatment (10 RCTs ( n  = 411): SMD = 0.70, 95% CI = 0.39–1.02) and at follow-up (8 RCTs ( n  = 289): SMD = 0.93, 95% CI = 0.34–1.52). Other activity assessments, including Wolf Motor Function Test, Box and Block Test, and Motor Activity Log, also revealed superior outcomes in the electrical stimulation group than those in the placebo group. Comparisons between three types of electrical stimulation (sensory, cyclic, and electromyography-triggered electrical stimulation) groups revealed no significant differences in the body function and activity. Conclusion: Electrical stimulation therapy can effectively improve the arm function in stroke patients.